2005
DOI: 10.1103/physrevlett.95.055701
|View full text |Cite
|
Sign up to set email alerts
|

Superfluid-Insulator Transition in a Commensurate One-Dimensional Bosonic System with Off-Diagonal Disorder

Abstract: We study the nature of the superfluid-insulator quantum phase transition in a one-dimensional system of lattice bosons with off-diagonal disorder in the limit of large integer filling factor. Monte Carlo simulations of two strongly disordered models show that the universality class of the transition in question is the same as that of the superfluid-Mott-insulator transition in a pure system. This result can be explained by disorder self-averaging in the superfluid phase and applicability of the standard quantu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 15 publications
2
29
1
Order By: Relevance
“…What happens for larger disorder or weaker interactions is still an open question. [23][24][25][26][27] One possibility is of course that the exponent remains universal along the whole line. In that case, there is most likely a unique Bose glass phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What happens for larger disorder or weaker interactions is still an open question. [23][24][25][26][27] One possibility is of course that the exponent remains universal along the whole line. In that case, there is most likely a unique Bose glass phase.…”
Section: Discussionmentioning
confidence: 99%
“…(42) can be evaluated in a series expansion in the small parameter δ that is defined in Eq. (23). The details of calculation are presented in Appendices A,B, and C, while here we state the final results.…”
mentioning
confidence: 99%
“…An older study [80] in 1d found a Kosterlitz-Thouless transition compatible with a universal Luttinger value (cf. [1,2]), but the disorder was too weak to see the physics mentioned in Ref.…”
Section: Significant Othersmentioning
confidence: 99%
“…hopping or interaction strengths, have remained largely unexplored until recently, when it was demonstrated that these can lead to qualitatively quite different phenomena [19,20,21]. In the quantum rotor model with off-diagonal disorder, the SF to MI transition takes place via an intermediate Mott glass (MG) phase [20,21]-a unique incompressible, yet gapless, glassy regime that was first reported in disordered fermions with extended range interactions [22]. It is thus of great interest to investigate whether such a phase also appears in the Bose-Hubbard model (BHM), and if particle-hole symmetry is essential for the stabilization of such a MG.…”
mentioning
confidence: 99%